Emergency department visits by children with and without autism spectrum disorder: An initial comparison evaluating multiple outcome measures at one urban children's hospital. (January 2015) - Casey, Laura Baylot; Williamson, Robert L.; Miller, Sarah; Smith, J. Brian; Frame, Kimberly N.; Langford, Elisabeth C.; Coleman, J. Brittain; Gilmore, Barry; McVicar, Kathryn A.
Highlights: Existing data of children with autism versus typically developing children from the emergency department of one children's hospital were analyzed. A significant association between the categories of presenting complaints and whether or not the patient had autism spectrum disorder was found. The arrival mode to the emergency department was not significantly different between those with and without autism spectrum disorder. No other significant differences were detected. Future research will investigate comorbid diagnoses, multiple sites, and will include a larger N . Abstract: Hospitals everywhere, especially children's hospitals, attempt to give exceptional care to all of their patients regardless of race, religion, socio-economic class, or intellectual ability. We evaluated data collected in the emergency department of a children's hospital, comparing duration of visit in minutes, chief complaint upon arrival to the emergency department, mode of arrival to the emergency department, method of obtaining patient history, demographic information, medications prescribed, medical testing, laboratory testing, diagnosis at discharge, billing code(s) used by the hospital per visit, and the type of insurance billed for services for patients with and without autism spectrum disorder. Results showed no differences were found between the presenting complaint provided by the caretaker upon entering the emergency department and the medical diagnosis for which the patient was actually treated within the emergency department. The tests also showed that there was a significant association between the categories of presenting complaints and whether or not the patient had autism spectrum disorder. The arrival mode to the emergency department was not significantly different between those with and without autism spectrum disorder. There was no significant difference existing between the two groups regarding cost of medical services provided and no significant difference existed between the two groups for the number of laboratory tests, medical tests, or total tests conducted, as well as no significant difference was found between the two groups was found in the length of hospital stay.